Bacterial Abundance, Diversity and Activity During Long-Term Colonization of Non-biodegradable and Biodegradable Plastics in Seawater - Odobel, Charlene; Dussud, Claire; Philip, Lena; Derippe, Gabrielle; Lauters, Marion; Eyheraguibel, Boris; Burgaud, Gaëtan; Ter Halle, Alexandra; Meistertzheim, Anne-Leila; Bruzaud, Stephane; Barbe, Valerie; Ghiglione, Jean-Francois (Frontiers in Microbiology, 2021)
The microorganisms living on plastics called “plastisphere” have been classically described as very abundant, highly diverse and very specific when compared to the surrounding environments, but their potential ability to biodegrade various plastic types in natural conditions have been poorly investigated. Here, we follow the successive phases of biofilm development and maturation after long-term immersion in seawater (7 months) on conventional (fossil-based polyethylene (PE) and polystyrene (PS)) and biodegradable plastics (biobased polylactic acid (PLA) and polyhydroxybutyrate-co-hydroxyvalerate (PHBV), or fossil-based polycaprolactone (PCL)), as well as on artificially-aged or non-aged PE without or with prooxidant additives (oxobiodegradable (OXO)). First, we confirmed that the classical primo-colonization and growth phases of the biofilms that occurred during the first 10 days of immersion in seawater were more or less independent of the plastic type. After only one month, we found congruent signs of biodegradation for some bio-based and also fossil-based materials. A continuous growth of the biofilm during the 7 months of observation (measured by epifluorescence microscopy and flow cytometry) was found on PHBV, PCL and artificially aged-OXO, together with a continuous increase in intra- (3H-leucine incorporation) and extracellular activities (lipase, aminopeptidase, β-glucosidase) as well as subsequent changes in biofilm diversity that became specific to each polymer type (16S rRNA metabarcoding). No sign of biodegradation was visible for PE, PS and PLA under our experimental conditions. We provide also a list of operational taxonomic units (OTUs) potentially involved in the biodegradation of these polymers under natural seawater conditions, such as Pseudohongiella sp. and Marinobacter sp. on PCL, Marinicella litoralis and Celeribacter sp. on PHBV or Myxococcales on artificially-aged OXO. This study opens new routes for a deeper understanding of the polymers biodegradability in seawaters, especially when considering alternative to conventional fossil-based plastics.